Comparison of BacT/Alert Blood Culture Systems With Conventional Methods for Culturing Normally Sterile Body Fluids Other Than Blood. (Annals of Medical Research, 2021)
None
Keywords: Sterile Body Fluids, BacT/Alert Blood Culture System